Gestión del turismo en Áreas Naturales Protegidas - Romo Román, Pablo César (Pontificia Universidad Católica del Perú, 2019)
Tourism in Natural Protected Areas (ANP) has increased in recent years and the trend is that it continues to do so. This has been beneficial, mainly economic and social, but at the same time, a worldwide concern has arisen from the environmental consequences that development can produce in these natural spaces. Currently, there are protected natural areas that receive a number of visitors unthinkable in the past, and seasonally resemble mass tourism destinations, which previously only arise in beaches and cities, as is the case of the model of tourist development of the city of Cancun. In Peru, there is also tourism in ANP that comes to generate the benefits mentioned previously, and despite this, there is a large investment gap to achieve proper management of them. This need for investment translates into a diversity of limitations that negatively influence the management of this spaces and therefore the sustainability and long-term permanence of tourism activity. It is so, from a good management in the conservation of the ANP that includes a good tourist management, these spaces have the potential to ensure in perpetuity the realization of tourist activities that generate benefits for entrepreneurs, local community and also opportunities for recreation of tourists and local community. In this sense, various actions are required to improve tourism management of these sites, from the increase in the budget of the entity responsible for its administration, as well as a prioritization of the entity in charge of tourism policy at the national level.This article will address the relevance of protected natural spaces in the tourism sector, as well as the challenges for the sustainability of the activity and those spaces. Consequently, it will address some international cases and the reality of the issue at the national level; to finally provide the conclusions of the analysis and the proposals to improve public policy.

El turismo en Áreas Naturales Protegidas (ANP) se ha incrementado en los últimos años y la tendencia es que lo siga haciendo. Dicha realidad ha producido diversos beneficios, principalmente económicos y sociales; sin embargo, al mismo tiempo ha surgido una preocupación a nivel mundial por las consecuencias ambientales que el desarrollo turístico podría producir en estos espacios naturales. Es así que, a partir de una buena gestión en la conservación del ANP que incluye una buena gestión turística, estos espacios tienen el potencial de asegurar a perpetuidad la realización de actividades turísticas que generen beneficios para empresarios, comunidad local y además sean espacios para la recreación de turistas y comunidad local. En ese sentido, se requieren diversas acciones que permitan mejorar la gestión turística de estos espacios, desde el incremento de presupuesto de la entidad competente en su administración, así como una priorización de la entidad a cargo de la política turística a nivel nacional.El presente artículo abordará la relevancia que tienen los espacios naturales protegidos en el sector turismo, así como los retos para la sostenibilidad de la actividad y de dichos espacios. Consecuentemente, se abordará algunos casos internacionales y la realidad de tema a nivel nacional, para finalmente brindar las conclusiones del análisis y las propuestas de mejora de la política pública.
Tourism management in protected areas
Keywords: Turismo sostenible; áreas naturales protegidas; Gestión de áreas protegidas; https://purl.org/pe-repo/ocde/ford#5.02.04